ANOTHER EXAMPLE OF ? P W VAR MEXICANA AND ASSOCIATED FOSSILS FROM COAHUILA - MALDONADO KOERDELL, MANUEL (Laboratorios Hormona S A, CD MEXICO, DF, MEX, 1941)
Citrus foliage infested with Aleurocanthus woglumi was used at Cuernavaca, Morelos, to determine the effectiveness of the parasite E serius The studies show that parasitization builds up to as high as 85% by the end of the rainy season in Oct, dropping
CIENC MEX
Keywords: EXAMPLE, P W VAR MEXICANA, ASSOCIATED FOSSILS, COAHUILA; MULTIDISCIPLINARIA; PALEONTOLOGIA; PALEONTOLOGIA ANIMAL